Kontribusi Kompetensi Profesional Guru Terhadap Hasil Belajar Siswa pada Mata Pelajaran Instalasi Motor Listrik - Fegie Anjansani; Aswardi Aswardi (Jurnal Pendidikan Teknik Elektro, 2023)
This study aims to find out how much the contribution of teacher professional competence is to student learning outcomes in the subject of electric motor installation at SMK N 5 Padang. This type of research is a quantitative descriptive research that is correlational. The population in this study were grade 2 students at SMK N 5 Padang for the 2022/2023 academic year. The test of the questionnaire instrument was carried out to 30 students in class 2 TITL. To determine the validity of the questionnaire, the product moment correlation formula was used with a significance level of 5%, 9 items were found to be invalid and a reliability test was carried out using the alpha coefficient formula by comparing the r product table moment significance level of 5%. The sampling technique used proportionate stratified random sampling with a total of 38 students. Collecting data in this study using the questionnaire instrument method and assessing student performance as measured by a Likert scale with data analysis using correlation coefficient analysis techniques and the significance of the correlation using the t-test. The results show that (1) there is a positive and strong correlation between teacher professional competence and student learning outcomes (2) there is a significant relationship between teacher professional competence and learning outcomes (3) the magnitude of the contribution of teacher professional competence to student learning outcomes in Installation subject Electric Motors obtained by 36.12%.